The warning [compact disc, unabridged] - Patterson, James, 1947-; Wells, Robison E (Hachette Audio, 2019)
One year after a power-plant accident forces a small town to evacuate completely, Jordan returns with his family, but the town is mysteriously cut off from television and the Internet and the military will not let people enter or leave.